Stakeholder perceptions on visitors' centre as a strategic tool for engagement: lessons from a power station visitors' centre in the Vaal region - Ntsabiseng, Teboho (Vaal University of Technology, 2021)
Relationships are important for building good reputation for the organisation. The purpose of the study was to explore stakeholders’ perceptions on visitors’ centre as a strategic tool for engagement. The study followed a qualitative approach and data was collected using semi-structured interviews and a sample of fifteen (15) participants was randomly selected. The results showed that the visitors’ centre is perceived by stakeholders as being an important establishment, and that face-to-face interaction or engagement with employees is important. It therefore appears that the centre serves as a hub of information; where individuals learn about a very large entity where information is collected and packaged in a comprehensive manner that creates mutual understanding between stakeholders and the organisation. However; the findings also revealed that, for the visitors’ centres to be successful in implementing their strategies of becoming a one-stop shop for stakeholders and delivering user-friendly messages about the organisation; the entity need to consider the ever-changing technological advancements such as using 3D and interactive models that will excite the public.
M. Tech. (Department of Public Relations Management, Faculty of Human Sciences), Vaal University of Technology.
Keywords: Public relationships; Stakeholders perceptions on visitors; Visitors' centres; User-friendly; Organisations interaction; Organisational communication; Dissertations, Academic -- South Africa.; Public relations -- South Africa.; Business ethics -- South Africa.